Computational studies on thermal stability of Endoglucanase - Ibrahim Ali , Noorbatcha; Waesoho, Shukree; Hamzah, Mohd. Salleh (2012)

(untitled)
Enhancing the functionalities and properties of enzymes via computational prediction is an emerging technology. In order to design new thermostable enzymes, we have employed molecular dynamics (MD) simulation techniques to find out the dynamics factors responsible for the thermal stability of known endoglucanases (EG). Mesophilic endoglucanases from Fusarium oxysporum (EGFO) and thermophilic endoglucanase from Humicola insolens (EGHI) with known crystal structures and enzyme activity, are used to compare their dynamical behaviors at 40°C and 60°C using MD simulation in aqueous media. It has been found that the Root Mean Square Derivation (RMSD) backbone of EGFO tends to increase more rapidly at higher temperatures, where as the RMSD values for EGHI either remains similar or decreases at higher temperature. The RMSD helices of EGFO also have the behavior similar to that RMSD backbone. The secondary structure conformation at the residues position 225 to 231 of EGFO changes significantly at higher temperature where as conformation of EGFO at these positions is maintained as the temperature is increased. The EGHI shows salt-bridge interactions and hydrophobic interactions in these regions. Hence we propose these two factors are crucial for the thermal stability of endoglucanase. Using this information we have carried out several in silico mutations on EGFO with the objective of designing more thermostable endoglucanase and found that the dynamic behavior of newly designed mutants are consistent with our conclusions. We propose that the new quintuple mutant obtaining by mutating at the positions T224E/G229A/S230F/S231E/N321R is more themostable than EGFO or EGHI.